DETERMINING AUTOMATION EFFECT ON MARKET EFFICIENCY - Asewe Stephen; Robert Mule; Peter Ndichu; Fredrick Onyango Aila; Alecia Elizabeth Ochido Okungu; Micheal Munene Michoki; Dancan Mayieka Onchonga; Gideon Momanyi (European Scientific Journal, ESJ, 2013)
The aim of this research was to better understand technology-induced market changes. The Nairobi Security Exchange was studied and the effects of an automation exercise carried out in 2006, was the research focus. Adoption of case study unraveled how automation impacts efficiency. Secondary data in form of monthly NSE-20 share index from January 2001- December 2011 and transformed into compounded monthly return was used. Run test was then applied. Too many runs indicate a tendency for high and low values to alternate; it was found that returns were normally distributed. As such, a normality test was conducted on the NSE using mean, skewness and kurtosis. Considering the mean and median, the two measures were close , and in almost all the years the skewness was close to zero (0) as well as the kurtosis close to three (3) all this shows that the data was normally distributed which confirmed that the market was weak form efficiency. Finally, t statistics showed that there was a statistical significant difference between manual and automation in the stock market performance during the year of transition, 2005 to 2006 a P value of 0.0006 when it was fully implemented, implying that there was a difference in the market performance before and after market automation. These findings are meant to provide an understanding of the automation implication undertaken by market authorities that’s CMA and NSE on the market performance. It will assist investors to develop strategies relating to their operational environment.